Humanitarian Athletic Participation and Identity Work - Terrell, Amanda; Houltberg, Benjamin; Brown, Sarah; Falco, Rachel; Schnitker, Sarah (Frontiers in Sports and Active Living, 2021)
Numerous studies examine youth purpose and volunteerism, but only few investigate how altruistic activities shape identity development within athletic contexts. Endurance-based humanitarian fundraising teams are becoming increasingly popular forms of volunteerism among adolescents and young adults in the United States, but little is known about their developmental role. Twenty-four participants (15–21 years of age; M = 17.42) were interviewed to identify the prominent themes that arose from their experiences while training for and participating in a marathon. A thematic analysis was used to determine the dominant themes that characterized the intersection of humanitarian marathon training and running with aspects of identity work. The majority of the comments of the participants were directly tied to their experiences in running the marathon. Four themes were identified including identity work, faith, purpose, and social connection. More so than exploring their possible selves, a consistent theme throughout the interview with the participants was what they learned about their current selves and the capacities they already possessed during their marathon experience.